Limited Trial of 3D Map Integrated Mobile Learning App for Ecology and Conservation Education in the Eastern Aceh Region of the Leuser Ecosystem - Armanda, Fahmy; Aprilia Putri, Kartika; Saumi, Fazrina (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Environmental degradation and biodiversity loss in the Leuser Ecosystem highlight the urgent need for effective ecology and conservation education that is contextually grounded and technologically supported. This study aims to develop and evaluate a mobile learning application integrated with 3D map visualization to support ecology and conservation education in the Eastern Aceh region of the Leuser Ecosystem. The research adopted a research and development approach using the ADDIE model, with the present study focusing on the implementation stage through a limited trial. The validity of the developed media was evaluated by experts in content, instructional design, media, and language, while practicality was assessed through user responses involving university students and senior high school students. The validation results showed high levels of validity, with average scores of 84% for content validity, 81% for instructional validity, 87% for media validity, and 87% for language validity, indicating that the application is highly valid. Practicality testing also yielded very high results, with an overall practicality score of 86%, demonstrating that the application is easy to use, efficient, attractive, and supportive of the learning process. These findings indicate that the 3D map integrated mobile learning application is both valid and practical for use in ecology and conservation education. The study contributes to the development of technology enhanced conservation learning media and provides a foundation for broader implementation and further effectiveness testing in diverse educational settings.